2016
DOI: 10.1155/2016/9707292
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Glutathione Biosynthesis Contributes to Oxidative Stress and Liver Dysfunction in Acute Kidney Injury

Abstract: Ischemia-reperfusion is a common cause for acute kidney injury and can lead to distant organ dysfunction. Glutathione is a major endogenous antioxidant and its depletion directly correlates to ischemia-reperfusion injury. The liver has high capacity for producing glutathione and is a key organ in modulating local and systemic redox balance. In the present study, we investigated the mechanism by which kidney ischemia-reperfusion led to glutathione depletion and oxidative stress. The left kidney of Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 65 publications
5
55
0
Order By: Relevance
“…The reduction in GSH and GSSG levels could be a compensatory mechanism by which the rats fed the formulated feed mixed with crude oil contaminated catfish to overcome the effect of the oxidant stress caused by free radicals produced by crude petroleum oil. The is in line with the findings of Shang et al (2016), indicating that the decrease in GSH to GSSG ratio in the blood implies that oxidative stress occurred in the distant organs due to crude petroleum oil induced toxicity. No significant difference were observed in the blood GSH, GSSG and GSH : GSSG ratio when rats fed CPO-CCD only were compared with rats fed CPO-CCD + tween 80.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The reduction in GSH and GSSG levels could be a compensatory mechanism by which the rats fed the formulated feed mixed with crude oil contaminated catfish to overcome the effect of the oxidant stress caused by free radicals produced by crude petroleum oil. The is in line with the findings of Shang et al (2016), indicating that the decrease in GSH to GSSG ratio in the blood implies that oxidative stress occurred in the distant organs due to crude petroleum oil induced toxicity. No significant difference were observed in the blood GSH, GSSG and GSH : GSSG ratio when rats fed CPO-CCD only were compared with rats fed CPO-CCD + tween 80.…”
Section: Resultssupporting
confidence: 90%
“…No significant difference was seen in GSH level in the brain of all the experimental groups. The reduction in GSH level in the kidney and liver of rats fed CPO-CCD only (Table 2) may be due to the decrease in the activity of the hepatic glutamate-cysteine ligase (a key enzyme responsible for glutathione synthesis) (Shang et al (2016). The depletion in brain GSH level of rats fed CPO-CCD may lead to increased production of superoxide, hydroxyl radicals, and hydrogen peroxide, because there is no known enzymatic defense against hydroxyl radicals (Dringen, 2000), making GSH the only compound capable of scavenging these radicals in the brain.…”
Section: Resultsmentioning
confidence: 99%
“…In a murine experimental model, mice overexpressing GPX4 are protected against oxidative stress [ 31 ], and administration of glutathione, the main substrate of GPX4, attenuates IRI after warm ischemia [ 32 , 33 ]. These results were furthermore confirmed by Shang et al providing evidence in 2016 that impaired glutathione biosynthesis was associated with a higher level of oxidative stress and hence with a higher impact of IRI on liver damage [ 34 ]. Analysis of the downstream pathway using selective knockout mice showed that GPX4 controls lipid peroxidation presumably via regulation of 12/15-lipoxygenase activity which in turn was shown to contribute to cell death [ 26 ].…”
Section: Introductionsupporting
confidence: 65%
“…Reactive oxygen species and oxidative stress are also important players in AKI-induced liver injury. Renal ischemiareperfusion (IR) reduces glutathione levels in the liver and blood through the inhibition of glutamate-cysteine ligase, the first rate-limiting enzyme of glutathione synthesis (Shang et al, 2016). Lipid peroxidation is also increased in the liver as evidenced by the elevated level of malondialdehyde.…”
Section: Introductionmentioning
confidence: 99%